Применение биометрических методов распознавания личности в банковской сфере и направления повышения эффективности этих методов - Крамаренко, В.Н. (Культура народов Причерноморья, 2013)
Статья посвящена анализу биометрических методов распознавания личности применительно к банковской сфере деятельности и обоснованию перспективных направлений развития этих методов. В работе проведен анализ перспективных биометрических методов распознавания личности, систематизированы требования к данным методам, исходя из специфики банковской деятельности и выявлены параметры биометрических систем, требующие улучшения. Представляя процесс распознавания личности в виде выполнения последовательных процедур, применяя подходы теории вероятностей, выявлены перспективные направления совершенствования биометрических систем распознавания личности. Стаття присвячена аналізу біометричних методів розпізнавання особистості стосовно до банківської сфери діяльності обґрунтуванню перспективних напрямів розвитку цих методів. У роботі проведено аналіз перспективних біометричних методів розпізнавання особистості, систематизовано вимоги до даних методам, виходячи із специфіки банківської діяльності та виявлено параметри біометричних систем, що потребують покращення. Представляючи процес розпізнавання особистості у вигляді виконання послідовних процедур, застосовуючи підходи теорії ймовірностей, виявлено перспективні напрями вдосконалення біометричних систем розпізнавання особистості. The article analyzes biometric methods of identity recognition applied to banking sector and proves prospective ways of developing and improving these methods. The analysis includes review and classification of biometric methods of identity recognition and the requirements to these methods in banking sector. The bottle necks of each method were identified. An identity recognition process is described and analyzed as a set of consecutive procedures. With the use of the approaches of the probability theory, the prospective methods of improving the efficiency of identity recognition were estimated. Based on these models the nature of errors of biometric recognition systems was explained (errors of the first type in comparison with the errors of the second type). The recommendations to reduce the errors of the first type were made. With the help of the developed approaches, efficiency of biometric system combination was estimated. It was shown that the use of the second method (channel), even with not very high biometric characteristics, but with a certain rule of adding (aggregation) approach will allow dramatically reducing the errors of the first and second types. The general recommendations allow choosing biometric techniques which are the most comfortable for customers, but in the same time they provide required levels of identity recognition.